Japan in the Russia - U.S. Relations - Volkov, S. V. (Vestnik MGIMO-Universiteta, 2015)
The article examines the impact of the crisis in Russia - U. S. relations in connection with the events surrounding Ukraine on the world system and its key component - the Asia-Pacific region where Japan plays a crucial role. The author assumes that the international relations have no common understanding of the rules of engagement between the USA, the Group of Seven, Russia and the BRICS countries. As a result, the leading countries of the world are guided by conflicting scenarios. The article deals with the American scenario in relation to China and the Russian Federation and the Russian one in relation to polycentric and the U. S. - centered world orders. The most important element of the American scenario in relation to Beijing is Japan. This country is central to Washington's policy to contain China. Tokyo is headed for the rapid rejection of pacifist principles of its foreign policy. Russian scenario for the international system is in an active course to establishing a polycentric world order. United States' scenario against Russia in this regard is a containment strategy of Moscow. The central component of this strategy, as it can be assumed, is a violation of the strategic balance in US - Russian relations. However, Ukraine has become a major springboard to contain Russia. Instead of establishing equal Russian - American relations United States and their allies (under American pression) have chosen a policy of isolating Moscow, but such actions are blocking the Russian - Japanese rapprochement beneficial both for Tokyo and Kremlin, which is interested in deepening its ties with Japan in order to diversify its relations with Asia-Pacific area. The author concludes that the long-term interests of Russia and Japan dictate both sides to move closer, but the policy of the U.S. administration towards Russia on the Ukranian question blocks this possibility.